STUDI ANALISIS PUTUSAN PENGADILAN AGAMA JAKARTA SELATAN NO. 1751/P/1989 TENTANG PERKAWINAN MELALUI TELEPON - Muhajir, Muhajir (Al-Qadha, 2018)
The legal basis of marriage law in Indonesia Constitution No. 1 of 1974 concerning Marriage and Compilation of Islamic law which is a reduction of Islamic rules regarding marriage, divorce, representation and inheritance originating from classical Islamic jurisprudence literature from various schools which are summarized and adapted to the needs of the people of Indonesia. The two legal bases regarding the marriage are expected to be a legal basis for the Indonesian people who will carry out the marriage. But in the practice of implementing marriage in the community, many new things appear that are ijtihad because there are no rules specifically set out to regulate such matters such as marriage through telephone.